2018
DOI: 10.1186/s12891-018-2057-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between Fas/FasL gene polymorphism and musculoskeletal degenerative diseases: a meta-analysis

Abstract: BackgroundIt was reported that Fas (rs1800682, rs2234767) and FasL (rs5030772, rs763110) gene polymorphism might be related to the risk of musculoskeletal degenerative diseases (MSDD), such as osteoarthritis (OA), intervertebral disc degeneration (IVDD) and rheumatoid arthritis (RA). However, data from different studies was inconsistent. Here we aim to elaborately summarize and explore the association between the Fas (rs1800682, rs2234767) and FasL (rs5030772, rs763110) and MSDD.MethodsLiteratures were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Polymorphisms in FAS gene may decrease the apoptotic potential of the receptor, and have been associated with several illnesses, including cancer and musculoskeletal degenerative disorders [100,101]. Furthermore, there are studies demonstrating the association of FAS polymorphisms with the persistence of HTLV infections and its clinical manifestations, such as Adult T-Cell Leukemia (ATL) and HTLV-1-associated myelopathy (HAM) [102,103,104].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…Polymorphisms in FAS gene may decrease the apoptotic potential of the receptor, and have been associated with several illnesses, including cancer and musculoskeletal degenerative disorders [100,101]. Furthermore, there are studies demonstrating the association of FAS polymorphisms with the persistence of HTLV infections and its clinical manifestations, such as Adult T-Cell Leukemia (ATL) and HTLV-1-associated myelopathy (HAM) [102,103,104].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…Activated caspase-8 activates downstream caspase-3 to trigger the caspase apoptosis cascade and promote cell apoptosis ( Figure 2 ). Some researchers have revealed a close association between Fas/FasL gene polymorphisms and musculoskeletal degenerative diseases through meta-analysis, among which the Fas (rs1800682) and FasL (rs763110) polymorphisms are associated with the susceptibility to IVDD [ 58 ]. In herniated lumbar IVDs, IVD cells activate the Fas/FasL signaling pathway to promote IVD cell apoptosis through autocrine or paracrine FasL [ 59 ], and Fas may be involved in apoptosis of notochord cells in NP [ 60 ].…”
Section: Link Between Caspase Family and Apoptosis In Ivddmentioning
confidence: 99%
“…Since FasL expression in IDD is reduced, most scholars believe that FasL expression by NPCs has a protective effect on IVDs 44 . Huang et al 45 reported that the Fas G allele (rs1800682) increased the risk of IDD, and the FasL T allele (rs763110) had the opposite effect. However, there are different views: FasL is harmful to IVDs 46 .…”
Section: The Death Receptor Pathway and Iddmentioning
confidence: 99%